Anti Bacterial Activity Test of Ethanol Extract of Papaya Leaves (Carica papaya L) on the Growth of Staphylococcus epedermidis - Jon Kenedy Marpaung; Suryani, Monica; Ivan Elisabeth Purba (Sean Institute, 2022)
Papaya is a tropical plant from the Caricaceae family, botanically defined as Carica papaya L. Traditional use of papaya leaves is to prevent bleeding in wounds and to treat wounds, lower high blood pressure, treat dengue fever, eliminate acne and smooth the skin and digestive disorders. Staphylococcus epidermidis is a Gram-positive bacterium, immobile, non-sporing, in solid culture media in the form of cocci in irregular groups, the arrangement is similar to grapes, prominent, shiny, does not produce pigment, white in color. Staphylococcus epidermidis bacteria can cause swelling (abscess) diseases such as acne, skin infections, urinary tract infections and swelling of the kidneys. This study was conducted with the aim of knowing the antibacterial activity of the ethanol extract of papaya leaves (Carica papaya L) with concentrations of 5%, 10%, 15%, and 20% against the growth of Staphylococcus epidermidis bacteria. This research method used an experimental method, namely to determine the antibacterial activity of the ethanol extract of papaya leaves (Carica papaya L) against the growth of Staphylococus epidermidis bacteria. This research used 96% ethanol as solvent. The test was carried out through several stages including material collection, preparation of simplicia, manufacture of ethanol extract from papaya leaves by maceration and testing of antibacterial activity against Staphylococus epidermidis bacteria. Based on the results of the phytochemical screening test of the thick extract, papaya leaves contain a class of alkaloid compounds, flavonoids, saponins, steroids/triterpenoids and tannins. The results of the antibacterial activity test of thick papaya leaf extract against Staphylococus epidermidis bacteria had an average inhibitory activity at concentrations of 5% (7.33 mm), 10% (8.44 mm), 15% (9.44 mm) and 20 % (10.3mm). As a comparison, Cloramfenocol 30 g was used to produce an inhibitory power of 32.1 mm and the best results obtained were at a concentration of 20% which had an inhibitory power of 10.3 mm.